Learning Model Of Dribbling Futsal Ball Game Based For Junior High School Students - Cahya Setia; Ardian Cahyadi (UNIB Press, 2020)
This research research and development aims to produce a Learning model of dribbling futsal ball game-based for junior high school students. In addition, this research and development is carried out to obtain in depth information about development and application of Futsal herding models for junior high school student and to find out the effectiveness, efficiency, also attractiveness of children to models created. This study uses Research & Development (R & D) development research method from Borg and Gall. The subjects in this research and development were junior high school students consisting of 60 children. The instruments used were questionnaires, questionnaires, and futsal dribbling test instruments used to collect volleyball bottom service data for junior high school aged student, while the stages in this research and development were: (1) needs analysis, (2) expert evaluation (initial product evaluation); (3) limited trials (small group trials); and (4) main testing (field testing). The model effectiveness test uses the futsal ball dribbling skill to determine the level of ability to dribble a futsal ball for junior high school age before giving a treatment in the form of a dribbling model developed and to determine the level of ability to dribble after the dribbling model treatment or treatments developed, from the initial tests performed dribbling a student ball of 750, Based on the development results, it can be concluded that: (1) By futsal dribbling learning model for junior high school age, it can be developed and applied in physical education learning at school (2) By futsal dribbling learning model for junior high school age that has been developed, evidence of an increase is obtained. This is shown in the testing results from pretest and posttest data that there is a significant difference between before and after the treatment model.